Analysis of the Phenomenon of Student Discipline Problems in the Learning Process - Ambelia, Risa; Muhaimin, Abdul; Ritonga, syahdanu Putra; Sucierawati, Tria (International Journal of Education and Teaching Zone, 2023)
This study seeks to reveal the discipline of students in the learning process. This type of research is descriptive qualitative. Descriptive qualitative is a method based on a philosophical understanding used to research an object with actual conditions, not settings or experiments; the researcher is an instrument. The subject of this study was the Islamic boarding school Persulukan Al-Hasanah Jambi Branch II, where the population in this study numbered 20 students and five teachers. The samples in this study were ten students and two teachers who were taken using the purposive sampling method. Purposive sampling is a technique for collecting data that is not random, and the researcher determines how to take the sample by determining the unique characteristics according to the objectives to be obtained from the research. Data collection techniques in this study were carried out using documentation and special interviews for one semester of learning, which were then analyzed and conclusions drawn. As for the results that have been carried out, it is found that there are three factors of students' indiscipline, namely skipping (20%), being late (50%), and not memorizing (30%)